Les temporalités frontalières et urbaines du port de Strasbourg. Analyse géohistorique d’une relation fluviale ville-port - Antoine Beyer; Jean Debrie (Métropoles)
The geo-historical approach to the relation port-city in the case of Strasbourg (France) implies to consider at the same time two chronologies. On the one hand, the geopolitical dimension with a city leaned on the french-german border. On the other hand, the more common economic development with the connection and the de-connection phases of the two functional spaces involved, i.e. port and urban spaces. In such a perspective, the paper will develop alternatively the way the port grew in a political unstable context, and replace its developement in the shaping of the global urbanization. Those two topics will in return differenciate two geographical scales, the regional environment and the more local urban planning strategies.